Importance of size-selective particle sampling for assessing occupational exposures: results from three different occupational settings - Viegas, Susana (2016)
Sampling the total air concentration of particulate matter (PM) only provides a basic estimate of exposure that normally not allows correlating with the observed health effects. Therefore is of extreme importance to know the particles size distribution and, in more detail, the exposure to fine particles (≤ 2.5 µm). This particles dimension corresponds to the respirable fraction. This particle fraction can result, besides local effects, in systemic effects due to particle deposition and clearance from the lungs and transport within the organism. This study intended to describe occupational exposure to PM2.5 in three different units located near Lisbon and related with occupational exposure to organic dust, namely: swine and poultry feed production and waste management.